Efeito do extrato de Dichrostachys glomerata (forssk.) Chiov. no peso corporal e em marcadores cardiometabólicos em mulheres na pós-menopausa: ensaio clínico randomizado, duplo cego - Castro, Vanessa de Souza (2024)
Menopause is a physiological event in middle-aged women that marks the end of their reproductive years, defined as the permanent cessation of menstruation, considering a minimum of twelve months of amenorrhea. This period is marked by hormonal changes that, in addition to affecting the quality of life, are related to cardiovascular, skeletal, changes in the lipid metabolism of adipose tissue, and body composition. Therefore, there is an increased risk for the development of cardiovascular diseases, type 2 diabetes mellitus, abdominal adiposity, dyslipidemias, and a greater likelihood of meeting the criteria for metabolic syndrome. The effects of hormone replacement therapy on women's health in the post-menopausal period are still highly controversial and indicate an increased risk for breast cancer. Various herbal products have been studied and used to treat metabolic disorders and control symptoms present in menopause. Thus, the main objective of this research was to evaluate the effects of treatment with Dichrostachys glomerata on body weight and cardiometabolic markers in post-menopausal women. This is a randomized, controlled, double-blind clinical trial conducted in a clinic in the east zone of São Paulo-SP, from May to September 2022. Women between 45 and 65 years of age, post-menopausal, with BMI > 24.9kg/m² were included. Participants were divided into two groups: the group treated with the herbal product (n=12) received, orally, 2 capsules/day containing 200 mg of Dichrostachys glomerata extract at 10% polyphenols each, and the placebo group (n=13) received, orally, 2 capsules/day containing 200 mg of starch each. There were 12 weeks of intervention, with three evaluation moments (week 0, week 6, and week 12) where questionnaires were applied to characterize epidemiological information, dietary intake (24-hour recall), and climacteric symptoms (Kupperman index); anthropometric parameters (weight, height, and abdominal circumference), blood pressure, and biochemical tests were evaluated. The Generalized Estimating Equations test was used to evaluate the effect of groups, time, and interaction. No intervention effect was found on anthropometric parameters, blood pressure, and biochemical markers. Time demonstrated a significant improvement in climacteric symptomatology in the placebo group. We conclude that the administration of 400mg daily of Dichrostachys glomerata may not be superior to placebo in reducing body weight and improving cardiometabolic markers in post-menopausal women with overweight.